The ductility of human rights - Luján Túpez, Manuel Estuardo (2016)
The rapid advance of time, technology and mass communication in computer networks, forces us to recognize that knowledge is expanding and increasingly universal. Human rights, beyond the differences we may have on their characteristic features, and even their genetic effects; and unlike local laws that tend more and more to specialize and make their competence exhaustive and totally delimited, they become more and more fundamental reasons of the legal system, causing validity to acts, processes and the effects that they cause, only if they are understood to be ductile, that is, capable of being filled with content in each case.